Slow panic? The regulation of salvia divinorum in Canada, 1991-2019 - Yaremko, Jeff (Deviant behavior, 2023)
Smoking a potent concentration of salvia divinorum (hereafter salvia) has the capacity to dissolve one’s ego and sense of self. Due to the catatonic state a strong dose of salvia produces, the substance has been considered alarming by claims-makers including politicians, media officials, police, and citizen groups. This paper examines news media accounts of salvia use in Canada and salvia’s regulation by the Canadian federal government. Providing a qualitative content analysis of newspaper articles spanning 1991-2019 regarding claims made about salvia, we draw from literature on moral panics and drugs to conceptualize the police and political response to salvia in Canada. We trace the shifting claims made by an array of claims-makers, showing how the focus changed from curiosity to claims about risk. The banning of salvia in Canada displays the hallmarks of a moral panic, though in this case the claims-making about the harm and risk of salvia went on for years before the substance was made illegal. We apply the notions of slow panic and panic policy to salvia regulation in Canada and reflect on the implications for literatures regarding drug panics and the new psychedelic renaissance.